PERAN POKDARWIS DALAM PENERAPAN SAPTA PESONA PANTAI PURNAMA KOTA DUMAI - Widiyana "; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Dumai city has many tourist attractions that can be visited by tourists, one of them isPurnama beach. Purnama beach management is done by a group of tourism awarenesscommunity called Pokdarwis Purnama. Pokdarwis Purnama conducted the applicationof Sapta Pesona at Pantai Purnama. In theory, the role of Pokdarwis in the applicationof Sapta Pesona at Purnama Beach Kota Dumai in this thesis explains how theapplication of Sapta Pesona at the planning, implementation and utilization stage atPurnama beach of Dumai City. This study used a qualitative approach type researchstudy documentation. Data collection is done by interview, observation anddocumentation. Research subjects were key informants and additional informants. Theresults showed that Pokdarwis Purnama has been instrumental in applying SaptaPesona at Purnama beach at the planning stage. But for the implementation phase hasnot been fully implemented, due to constrained funding. While the utilization of thesocial and economic aspects can promote the welfare of local communities. It can alsodefend and reintroduce a culture that is almost forgotten.Keywords: role, pokdarwis, sapta pesona, beach, Dumai city.